The Cost of Hyperkalemia in the United States - Keith A. Betts; J. Michael Woolley; Fan Mu; Cheryl Xiang; Wenxi Tang; Eric Q. Wu (Kidney International Reports, 2018)
There are limited data on the cost of hyperkalemia. Methods: This retrospective analysis of the Truven MarketScan claims database assessed the economic burden of hyperkalemia among selected adult patients with hyperkalemia and matched controls. Results: A total of 39,626 cases (patients with hyperkalemia) were matched to 39,626 controls (patients without hyperkalemia) based on age, dialysis, chronic kidney disease (CKD) stage, heart failure, and renin-angiotensin aldosterone system inhibitor use. Compared with controls, cases incurred $4128 (95% confidence interval [CI] $3893–$4363) higher 30-day total health care costs ($5994 vs. $1865) and $15,983 (95% CI $15,026–$16,940) higher 1-year costs ($31,844 vs. $15,861). Among 11,221 matched pairs of patients with CKD and/or heart failure, cases incurred $5553 (95% CI $5059–$6047) higher 30-day total health care costs ($8165 vs. $2612) and $24,133 (95% CI $21,748–$26,518) higher 1-year costs ($48,994 vs. $24,861) than controls. The multivariable adjusted 1-year total health care cost difference was $15,606 (95% CI $14,648–$16,576) among all patients and $25,156 (95% CI $23,529–$26,757) among patients with CKD and/or heart failure. Cases had higher resource utilization rates including inpatient admissions (30-day: 0.14 vs. 0.03; 1-year: 0.44 vs. 0.19), outpatient visits (30-day: 3.33 vs. 2.28; 1-year: 26.58 vs. 18.53), and emergency department visits (30-day: 0.16 vs. 0.06; 1-year: 0.86 vs. 0.50) (all P < 0.001). When hospitalized, cases stayed 1.51 days (95% CI 1.22–1.80) longer and were 40% more likely to be readmitted. Conclusion: These data indicate that hyperkalemia is associated with a significant economic burden on afflicted patients and the health care system.